2005
DOI: 10.1016/j.cell.2005.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Germ-Layer Specification and Control of Cell Growth by Ectodermin, a Smad4 Ubiquitin Ligase

Abstract: TGF-beta signaling is essential for development and proliferative homeostasis. During embryogenesis, maternal determinants act in concert with TGF-beta signals to form mesoderm and endoderm. In contrast, ectoderm specification requires the TGF-beta response to be attenuated, although the mechanisms by which this is achieved remain unknown. In a functional screen for ectoderm determinants, we have identified Ectodermin (Ecto). In Xenopus embryos, Ecto is essential for the specification of the ectoderm and acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
316
3
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(337 citation statements)
references
References 31 publications
12
316
3
1
Order By: Relevance
“…Some of these VegT targets are involved in specifying endodermal fate (GATA4, -5, -6, and XSox17; Xanthos et al, 2001), while others establish boundaries between the mesoderm and endodermal areas (Mixer; Kofron et al, 2004). A third group includes signaling molecules and antagonists that are essential for mesodermal fate specification (Xnrs, chordin, FGFs, Antivin;Tanegashima et al, 2000;Kofron et al, 1999;Cha et al, 2006), while a fourth group of targets is negatively regulated by VegT and is required for ectodermal specification (ectodermin, Xema; Dupont et al, 2005;Mir et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these VegT targets are involved in specifying endodermal fate (GATA4, -5, -6, and XSox17; Xanthos et al, 2001), while others establish boundaries between the mesoderm and endodermal areas (Mixer; Kofron et al, 2004). A third group includes signaling molecules and antagonists that are essential for mesodermal fate specification (Xnrs, chordin, FGFs, Antivin;Tanegashima et al, 2000;Kofron et al, 1999;Cha et al, 2006), while a fourth group of targets is negatively regulated by VegT and is required for ectodermal specification (ectodermin, Xema; Dupont et al, 2005;Mir et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Smad4 lacks a PPXY motif to recruit the Smurfs, however, ectodermin/TIF1-γ (also named TIM33, RFG7 and PTC7), a protein harboring a RING domain in addition to a number of other functional domains, was reported recently to suppress Smad4 function and impair Xenopus embryonic development by acting as an E3 ubiquitin ligase of Smad4 [90]. This hypothesis is somewhat controversial, as another recent study in mammals did not find ectodermin/TIF1-γ functions in Smad4 degradation, but rather that ectodermin/TIF1-γ competes with Smad4 as a transcription cofactor of R-Smads and regulates the development of the hematopoietic system [91].…”
Section: Ubiquitinationmentioning
confidence: 99%
“…Dupont et al identified Ectodermin as a RING-type ubiquitin ligase for Smad4 which acts to control TGF-β and BMP signaling in Xenopus embryo development, ensuring correct developmental cell fate [86]. Depletion of Ectodermin or over-expression of Smad4 in the embryo marginal zone results in the same developmental phenotype, in agreement with the idea that Smad4 is a key Ectodermin target.…”
Section: Modifications Of Smad4 In Normal Cellsmentioning
confidence: 63%
“…Depletion of Ectodermin or over-expression of Smad4 in the embryo marginal zone results in the same developmental phenotype, in agreement with the idea that Smad4 is a key Ectodermin target. Strong biochemical evidence confirms Ectodermin is a ubiquitin E3 ligase for Smad4, and the authors further demonstrate a role for this ligase in limiting TGF-β-induced antiproliferative responses in human adult cells [86].…”
Section: Modifications Of Smad4 In Normal Cellsmentioning
confidence: 67%